Music, sound and the laboratory from 1750-1980 - Hui, Alexandra; Kursell, Julia; Jackson, Myles W. (Chicago The University of Chicago Press, 2013)
The understanding of sound underwent profound changes with the advent of laboratory science in the nineteenth and twentieth centuries. New techniques of sound visualization and detection, the use of electricity to generate sound, and the emergence of computers radically reshaped the science of acoustics and the practice of music. The essays in this volume of Osiris explore the manifold transformations of sound ranging from soundproof rooms to psychoacoustics of seismology to galvanic music to pedaling technique. They also discuss more general themes such as the nature of scientific evidence and the development of instruments and instrumentation. In examining the reciprocity between music and science, this volume reaches a new register in the evolution of scientific methodology during the nineteenth and twentieth centuries.